Phenological Restriction of the Oryza (v3) Model - Gutemberg Resende Honorio Filho; Alexandre Bryan Heinemann; David Henriques da Matta; Luís Fernando Stone; Santiago Vianna Cuadra; Silvio Steinmetz (Revista Brasileira de Meteorologia)
Abstract Photoperiod sensitivity affects the rice development cycle and its flowering. Crop simulation models, such as ORYZA (v3), use equations that depend on two main parameters calibrated by the user: sensitivity to photoperiod and minimum optimal photoperiod. Day length, determined by latitude and day of the year, also affects crop development. This study explores the interaction of these parameters in the ORYZA (v3) phenological model. When the optimum minimum photoperiod is shorter than the day length, photoperiod sensitivity delay or inhibit flowering. To ensure a proper simulation, these parameters need to be adjusted to avoid excessive prolongation of the vegetative phase. If calibrated incorrectly, or if let in constant low photoperiod conditions, the plant may remain in the vegetative state. The model presents challenges with cultivars that are highly sensitive to photoperiod in conditions where day length is constantly longer than the ideal minimum photoperiod. This situation may generate uninterpretable results and complicate the calibration of parameters via optimization algorithms. Therefore, it is crucial to properly adjust the optimal minimum photoperiod based on latitude and limit photoperiod sensitivity to ensure accurate and precise simulations of flowering.